Право собственности на домашних животных - Rudzis, Maria (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an evaluation of the pet ownership in the Russian civil law system. The author analyse that particular example of ownership, its subject and object with a special emphasis on the withdrawn.